Faktor-faktor yang Berhubungan dengan Kualitas Tidur Pasien dengan Lupus Eritematosus Sistemik - Andru, Gestana; Widhani, Alvina; Putranto, Rudi; Mansjoer, Arif; Shatri, Hamzah (UI Scholars Hub, 2024)
Introduction. Sleep disturbances are often found among Systemic Lupus Erythematosus (SLE) patients. Poor sleep may cause low quality of life. Study about sleep quality among SLE patients and related factors in Indonesia is scarce. This study aimed to know factors related to poor sleep quality among SLE patients. Methods. This cross-sectional study was conducted among SLE patients at Cipto Mangunkusumo Hospital Jakarta Indonesia. Sleep quality was assessed by Pittsburgh Sleep Quality Index (PSQI), with global PSQI score >5 indicates poor sleep quality. Factors evaluated were symptoms of depression and anxiety by Hospital Anxiety Depression Scale (HADS), pain by Visual Analogue Scale (VAS), Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), autonomic dysfunction by Low Frequency/High Frequency (LF/HF) ratio from Heart Rate Variability (HRV), and high sensitivity C-Reactive Protein (hs-CRP) level. Bivariate analysis was done by Chi Square or Fisher’s test. Multivariate analysis was done by logistic regression, p value <0.05 was considered statistically significant. Results. Total of 166 SLE patients were included. Mean age was 32.7 years old with the majority in age group of 21-30 years old and female. Poor sleep quality in SLE patients was found in 82.5% of subjects. Symptoms of depression were significantly associated with poor sleep quality in SLE patients, especially sleep efficiency. Anxiety was associated with subjective month- and week-long sleep quality, sleep disturbances, and sleep medication usage. Musculoskeletal component of the SLEDAI-2K was associated with month- and week-long sleep quality, sleep latency, and daytime dysfunction. Hematologic involvement was associated with daytime dysfunction, whereas mucocutaneous involvement was associated with sleep disturbances. Conclusions. Symptoms of depression were significantly associated with poor sleep quality in SLE patients, especially sleep efficiency. Anxiety was associated with subjective month- and week-long sleep quality, sleep disturbances, and sleep medication usage.